Sistem Informasi Pengobatan Tradisional di Unit Pelayanan Kesehatan Masyarakat (UPKM)/Community Development (CD) Bethesda Yayasan Kristen Kesehatan Umum (Yakkum) Area Sumba Timur Berbasis Mobile - Meske Silvia Upa Raji; Yustina Rada; Raynesta Mikaela Indri Malo (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This research emphasizes the importance of health for every individual, as good health facilitates daily activities. One crucial aspect of health is physical health, which includes being free from various diseases. With the increasing public interest in traditional medicine, the information regarding the public's knowledge about traditional medicine also needs to be enhanced. Therefore, this research aims to develop a mobile-based traditional medicine information system at UPKM/CD Bethesda YAKKUM as an information medium for the wider community. The method used for system development in this research is the waterfall method, which involves stages such as concept, design, data collection, creation, and testing. The developed application is a mobile-based traditional medicine information system, designed to help introduce traditional medicine in Indonesia. This application is designed to be easily accessible without the need to worry about internet connection or data charges, and it can be used in various regions. The result of this research is a mobile-based information system application that provides information about traditional medicine for various diseases. This application includes information on types of medicinal plants, their benefits, and explanatory videos, making it easier for the public to learn about and understand traditiona l medicine.